Ghrelin pretreatment enhanced the protective effect of bone marrow-derived mesenchymal stem cell-conditioned medium on lipopolysaccharide-induced endothelial cell injury. (15th May 2022) - Ge, Shanhui; He, Wanmei; Zhang, Lishan; Lin, Shan; Luo, Yuling; Chen, Qingui; Zeng, Mian
Abstract: Background: Lung endothelial barrier injury plays a crucial role in the pathophysiology of acute respiratory distress syndrome. It has been demonstrated that bone marrow-derived mesenchymal stem cells-conditioned medium (BMSCs-CM) and ghrelin have a protective effect. This study investigated if ghrelin pretreatment enhanced the protective effect of BMSCs-CM on lipopolysaccharide (LPS)-induced endothelial cell injury. Methods: BMSCs were isolated from rat bone marrow, expanded, then phenotypically tested for mesenchymal stem cell-identifying criteria by flow cytometry. The effects of the conditioned medium derived from ghrelin-pretreated BMSCs (BMSCs- ghrelin-pretreated -CM) on LPS-injured endothelial cells were evaluated by migration, apoptosis, permeability, and pro-inflammatory factor (e.g., tumor necrosis factor-α, interleukin (IL)-1β, and IL-6) assays in endothelial cells. Further, AKT/GSK3β pathway activation in endothelial cells was examined by Western blot, and the gene expression profiles of ghrelin-pretreated BMSCs were examined by RNA sequencing. Results: BMSCs- ghrelin-pretreated -CM had a greater protective effect on LPS-induced endothelial cell injury than BMSCs-CM by improving cell migration, alleviating apoptosis, and reducing endothelial permeability and the release of pro-inflammatory factors in endothelial cells. The mechanism is partly related to AKT/GSK3β pathway activation after BMSCs- ghrelin-pretreated -CM treatment. There were five upregulated candidate genes ( Wnt5a [i.e., Wnt Family Member 5A], S100b [i.e., S100 Calcium-Binding Protein B], Bmp2 [i.e., Bone Morphogenetic Protein 2], Id4 [i.e., Inhibitor Of DNA Binding 4], and PTHLH [i.e., Parathyroid Hormone Like Hormone]) in BMSCs after ghrelin treatment, and all were associated with AKT pathway activation and endothelial function. Conclusions: Ghrelin pretreatment enhanced the protective effect of BMSCs-CM on LPS-induced endothelial cell injury, partly by activating the AKT/GSK3β pathway. Highlights: Ghrelin pretreated MSCs exhibited better curative ability, but whether ghrelin treatment would improve the therapeutic effect of MSCs on endothelial injury remains unknown. MSCs pretreated with ghrelin markedly inhibited LPS-induced apoptosis and inflammation, and improved migration of endothelial cells, which was partly mediated by the activation of the AKT/GSK3β pathway. After ghrelin treatment, 88 upregulated and 405 downregulated genes were found in MSCs, among which Wnt5a, S100b, Bmp2, Id4, and PTHLH were associated with both AKT signaling pathways activation and endothelial function improvement.